A microeconomic model of worker motivation based on monetary and non-monetary incentives - Martin Petrick (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2018)
By focusing on direct monetary incentives, the traditional literature on motivating workers predicts that high-effort outcomes are unlikely unless workers become residual claimants of profit. However, real world employment contracts typically display a low incidence of profit sharing. In this paper, I extend the canonical model of a revenue sharing contract by integrating two more options for incentivising workers. The literature to date has discussed these strategies in isolation from each other. First, I assume that workers derive utility from following a work norm. The manager can influence workers' identification with a high-effort work norm at a cost. Second, workers risk being fired if they are observed shirking. Depending on the rigidity of their employment contract, this threat of termination induces them to increase effort. Key drivers of the optimal employment contract are then the variance of output, the costs of inducing worker's identification with high-effort norms and the rigidity of the labour market.
urn:nbn:de:gbv:3:2-96059
Keywords: 330